(untitled) (Malaysian Journal of Civil Engineering, 2018)
Seismic performance is obtained for a five-storied reinforced concrete frame building performing non-linear dynamic time history analyses. Performance of the building was obtained as a mean of fragility function of spectral acceleration. Earthquake ground motion records are selected from online source considering local earthquake faults scenario proposed in Comprehensive Disaster Management Program (CDMP) and then scaled to fit with Bangladesh National Building Code (BNBC) 1993 design response spectra. Since the structure is considered as typical reinforced concrete ordinary moment resisting frame located in Bangladesh, mechanical properties and other associated parameters are chosen according to Bangladeshi perspective. Each ground motion spectrum is matched with design code spectrum at fundamental time period of the building. Non-linear static pushover analysis is performed to determine damage states from pushover curve. Four damage states (from slight to collapse) are defined based on simplified assumptions. A set of dynamic time history analyses are carried out in order to obtain probability density function of the displacement demand correspond to different level of ground motions. Cumulative distribution of each associated damage states allows deriving fragility curves. Finally four fragility curves are obtained for four damge grades (slight, moderate, severe and collapse).